2013
DOI: 10.1101/gad.215293.113
|View full text |Cite
|
Sign up to set email alerts
|

Unliganded progesterone receptor-mediated targeting of an RNA-containing repressive complex silences a subset of hormone-inducible genes

Abstract: A close chromatin conformation precludes gene expression in eukaryotic cells. Genes activated by external cues have to overcome this repressive state by locally changing chromatin structure to a more open state. Although much is known about hormonal gene activation, how basal repression of regulated genes is targeted to the correct sites throughout the genome is not well understood. Here we report that in breast cancer cells, the unliganded progesterone receptor (PR) binds genomic sites and targets a repressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 81 publications
5
85
1
Order By: Relevance
“…1). 7 Already one minute after hormone treatment pPR interacts with and activates the CyclinA/CDK2 complex, which is recruited to regulated promoters and phosphorylates histone H1. 8 Hormone activated CDK2 also phosphorylates poly (ADP-ribose) polymerase 1 (PARP1), which converts NAD+ to poly(ADP-ribose) (PAR) attached to itself and to linker and core histones, facilitating displacement of histone H1.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancymentioning
confidence: 99%
“…1). 7 Already one minute after hormone treatment pPR interacts with and activates the CyclinA/CDK2 complex, which is recruited to regulated promoters and phosphorylates histone H1. 8 Hormone activated CDK2 also phosphorylates poly (ADP-ribose) polymerase 1 (PARP1), which converts NAD+ to poly(ADP-ribose) (PAR) attached to itself and to linker and core histones, facilitating displacement of histone H1.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancymentioning
confidence: 99%
“…Similarly, RNA-mediated recruitment of HP1γ to specific gene loci has been described in human cells [38]. Together with progesterone receptor (PR) and LSD1, HP1γ associates with a specific RNA known as steroid receptor RNA activator (RNA SRA) to repress a large set of hormone-inducible genes in the absence of ligand.…”
Section: Rnas Targeting Chromodomain Proteins To Specific Locimentioning
confidence: 99%
“…and a reader of the histone modification (e.g. Cbx7, HP1) in cis or in trans thereby recruiting these proteins to specific gene loci [16,33,38]. (C) Drosophila and/or mammalian HP1 binds to nascent mRNA of transcriptionally induced gene loci and/or directly interacts with active RNA polymerase II.…”
Section: Rnas Function In Recruitment Of Chromodomain Proteins To Larmentioning
confidence: 99%
“…It will also be important to determine the role of unliganded NRs in development as well as disease. An intriguing study has found that unliganded PR forms a repressor complex with a non-coding RNA and several epigenetic silencers including histone demethylases LSD1, KDM5B and histone deacetylases HDAC1/2 (Vicent et al 2013). In other words, unactivated PR maintains repressed chromatin structures at progesterone target gene enhancers, while the epigenetic landscape is reversed upon the interaction of PR with its ligand (Vicent et al 2013).…”
Section: Future Directionsmentioning
confidence: 99%